Socialization of forms of bullying behavior at the Mulia Medan Education Foundation - Junaidi Lubis; Leni Indrayani; Julia Maria; Muammar Rinaldi (Outline Journal of Community Development, 2024)
That the intended place of community service is an educational institution where in the foundation there is education starting from elementary school, junior high school, high schoolhigh school and vocational high school, that the Mulia Medan Foundation is essentially the same as foundations in general which have various problems like in general, school children will definitely experience various forms of obstacles, both from administration, daily behavior of students and others, where In this case it is also possible that there are various problems such as bullying at school and other problems, therefore the presence of community service from the Battuta University Law Study Program is expected to be able to provide a new glimmer of hope that bullying is something that can be detrimental and destructive for oneself. , other people and also those affected are the foundation or school itself, so the arrival of the Law Study Program provides knowledge for the future together that bullying is the enemy of education and the enemy of all of us, that by carrying out this community service, the implementers also hope for the best for foundation, students and all elements of the foundation to further prioritize humanist principles in dealing with various problems that arise in educational matters and overcome various problems that occur within the scope of education, and this bullying must be prioritized, never experienced by anyone, be it students, teachers, staff and others, that it is everyone's duty to work together to avoid bullying behavior at school. Based on the socialization that has been carried out, students are expected to be able to understand that bullying behavior is an act that cannot be justified and is not an act of joking or anything else, that bullying behavior, even if done in jest, will have a negative impact on the continuity of life in the future.